The Effectiveness of Family Psychoeducation Therapy to Improve the Quality of Life of Family Caregivers in Caring for Family Members Undergoing Hemodialysis - Uswatun Hasanah; Sapti Ayubbana; Supardi Supardi (Jurnal Ilmu Keperawatan Jiwa, 2020)
Caring for individuals with chronic illnesses can be stressful for family members. The majority of hemodialysis patients experience difficulty in carrying out their personal tasks so rely on family caregivers to carry out their daily activities. Family caregivers of hemodialysis patients bear a high burden of care that has a negative effect on their quality of life. This study aims to determine the effect of Family Psychoeducation Therapy (FPE) on the quality of life of the family caregiver in patients undergoing hemodialysis. The research design used was a quasi-experimental design pre-post test with control group. Sampling using random permutation with a sample size of 56 people with 28 family caregivers in the intervention group and 28 family caregivers in the control group. Measurement of quality of life data for family caregivers using the WHOQOL-BREF quality of life instrument. Data analysis used statistical test with t test. Family Psychoeducation Therapy was conducted in 5 sessions. The results showed that there were significant differences in the quality of life of family caregivers before and after Family Psychoeducation Therapy was carried out Therapy (p value 0.0001).